Multi-Response Optimization of Planting Process of a Seed Ridge Planter using Response Surface Methodology (RSM) - Yusuf, D. D.; Upahi, E. J.; Yusuf, H. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
The performance of a two- row self-propelled seed planter, Institute for Agricultural Research (IAR) single row animal drawn planter and the manual method of planting were investigated under laboratory and field conditions to optimise the planting process using Response Surface Methodology (RSM). Parameters optimisation of seed planting process becomes imperative in order to find parameter values that match predictions with reality and choose the right set of parameters that improve the performance of planter. Experiments conducted in this study were based on Central Composite Design (CCD), one of the designs in RSM Experimental treatments were three planting methods, three soil moisture levels, and three planting depths randomly assigned in a 3x3 factorial experiment arranged in a Randomized Complete Block Design (RCBD) in three replications. The results show increased plant population with increasing planting speed and moisture content values. Also, increased seedling emergence was observed with increasing moisture content and decreasing planting speed values. However, further increase in seed planting moisture content beyond the optimum point caused a decrease in the seedling emergence. Similarly, there was increased depth of planting with increasing seed planting speed and moisture content values. Further increase in soil moisture content beyond the optimum point caused a decrease in the depth of planting. Conclusively, soil moisture availability is an important factor affecting the depth of seed planting in the study area